FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN PELAYANAN POLI OBSGYN DI RSUD BANJARNEGARA - Yenni, Alfiati; Marwati, Triyani; Solikhah, Solikhah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2010)
Background: Banjarnegara Hospital is the only one of state hospital located in Banjarnegaracity. The surviving and competitive hospitals must provide the need of their consumer. So, thepatients can consider to use their health service. Based on the data of Banjarnegara hospitalmedical record noted that an increasing of the number of patient visit, especially in poli obsgyn.The interview of 10 poli obsgyn patients stated that they use poli obsgyn service because ofinformation about service quality and health facilities in Banjarnegara hospital. The purpose ofthis study was to detremine influencing factors of poli obsgyn service utilization in Banjarnegarahospital.Methods : This study was observational analytic research with cross sectional design.Research subjects were 77 respondents. The sample was taken with the purposive samplingtechnique to determine inclusion and exclusion criteria. Using data analysis is Chi Squarestatistical test.Results : Based on Chi Square test result shows: (1) there was a correlation betweenBanjarnegara hospitals existance information with utilization of poli obsgyn service which can beseen from Asymp. value. Sig <a (0.001 <0.05) and Chi Square count 11,866 > Chi Square table(df = 1 = 3.481). (2) There was a correlation between health service quality with poli obsgynservice utilization which can be seen from obasgun poly Asympt value. Sig < a (0.000 < 0.05)and Chi Square count 37,524 > Chi Square table (df = 1 = 3.481). (3) There was a correlationbetween health facilities with poly obsgyn service utilization which can be seen from Asymptvalue. Sig < a (0.000 <0.05) and Chi Square count 20,432 > Chi Square table (df = 1 = 3.481).Conclusion: There was a positive correlation between the information of Banjarnegara hospitalexistance, the quality of health services and health facilities to ward the utilization of services inBanjarnegara hospital poly obsgyn service.Keywords: utilization, services, poli obsgyn.